Conrad and history - Niland, Richard, 1978- (Oxford : Oxford University Press, 2010)
This text analyses the relationship between Conrad's work and three major subjects: the philosophy of history, nationalism (in Europe and Latin America), and Conrad's interest in French Romanticism and Napoleon Bonaparte.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Conrad, Joseph, -- 1857-1924 -- Criticism and interpretation; History in literature